INFLUENCE OF ANESTHESIA ON POSTOPERATIVE PERIOD AFTER UTERINE REMOVAL - Zhenilo, V.M.; Lebedeva, E.A.; Zdiruk, S.V.; Akimenko, T.I. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Medit͡s︡ina, 2017)
The present study is devoted to the development of anesthesia tactics for the purpose of early recovery of patients after amputation of the uterus and shortening of hospitalization. The algorithm of pre-operative examination of middle-aged patients with uterine myoma is proposed to select the optimal method of anesthesia, which allows to optimize the postoperative period in women with an increased risk of develop-ing severe pain syndrome and postoperative cognitive impairment. The study showed the advantage of regional anesthesia with dexmedetomidine sedation in the operation of amputation of the uterus in the form of a lower incidence of postoperative cognitive dysfunction syndrome, marked postoperative pain, as well as a reduction in hospitalization, which in turn allows rationalizing the economic costs of medical institutions, as well as improving the population's satisfaction quality of care.